2014
DOI: 10.1063/1.4900956
|View full text |Cite
|
Sign up to set email alerts
|

Gyrotactic trapping in laminar and turbulent Kolmogorov flow

Abstract: Phytoplankton patchiness, namely the heterogeneous distribution of microalgae over multiple spatial scales, dramatically impacts marine ecology. A spectacular example of such heterogeneity occurs in thin phytoplankton layers (TPLs), where large numbers of photosynthetic microorganisms are found within a small depth interval. Some species of motile phytoplankton can form TPLs by gyrotactic trapping due to the interplay of their particular swimming style (directed motion biased against gravity) and the transport… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
53
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 46 publications
6
53
1
Order By: Relevance
“…active particles do not cluster at specific lateral positions or focus in flow. In contrast, in the presence of swimmer-wall hydrodynamic interactions [210], bottom-heaviness [213], phototaxis [214,215], flexible body shape [216], or viscoelastic flows [217], the dynamics becomes dissipative in the sense of dynamical systems and particles aggregate at specific locations in the flow (see also the discussions in [211,218,219]). Although swinging and tumbling trajectories in microchannel Poiseuille flow have been observed experimentally with biological microswimmers [212,220], they have not yet been confirmed in experiments with active colloids.…”
Section: Motion In External Fluid Flowmentioning
confidence: 99%
“…active particles do not cluster at specific lateral positions or focus in flow. In contrast, in the presence of swimmer-wall hydrodynamic interactions [210], bottom-heaviness [213], phototaxis [214,215], flexible body shape [216], or viscoelastic flows [217], the dynamics becomes dissipative in the sense of dynamical systems and particles aggregate at specific locations in the flow (see also the discussions in [211,218,219]). Although swinging and tumbling trajectories in microchannel Poiseuille flow have been observed experimentally with biological microswimmers [212,220], they have not yet been confirmed in experiments with active colloids.…”
Section: Motion In External Fluid Flowmentioning
confidence: 99%
“…Numerical and experimental works have revealed how gyrotactic motility, combined with the presence of a flow, generates strongly inhomogeneous distributions. In the case of laminar flow, gyrotaxis produces a beamlike accumulation in downwelling pipe flows [11], while in horizontal shear flow it generates accumulation in thin layers [10,15,16]. Recent works have shown that gyrotaxis also produces clustering at very small scales (comparable with the Kolmogorov scale) in nonstationary turbulent flows [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, an interesting feature to understand is how the coupling between flow and motility occurs [5,6]. This question has been addressed for instance in the case of gyrotactic algae in a flow [7,8]. Because of the eccentric location of their chloroplast, these algae are subject to a torque induced by gravity and consequently tend to swim upward.…”
mentioning
confidence: 99%
“…Because of the eccentric location of their chloroplast, these algae are subject to a torque induced by gravity and consequently tend to swim upward. Gyrotactic algae have been shown to concentrate in downwelling regions of turbulent flows [8]; this is a direct consequence of the migration of gyrotactic algae towards low vorticity regions as shown by Kessler [7].…”
mentioning
confidence: 99%